Insights Into the Role of Epigenetic Factors Determining the Estrogen Response in Estrogen-Positive Ovarian Cancer and Prospects of Combining Epi-Drugs With Endocrine Therapy - Sarwar, Sadia; Alamro, Abir; Huq, Fazlul; Alghamdi, Amani (Frontiers in Genetics, 2022)
Ovarian cancer is one of the most lethal malignancies. The population at the risk is continually on the rise due to the acquired drug resistance, high relapse rate, incomplete knowledge of the etiology, cross-talk with other gynecological malignancies, and diagnosis at an advanced stage. Most ovarian tumors are thought to arise in surface epithelium somehow in response to changes in the hormonal environment. Prolonged treatment with hormone replacement therapy (HRT) is also considered a contributing factor. Estrogens influence the etiology and progression of the endocrine/hormone-responsive cancers in a patient-specific manner. The concept of hormonal manipulations got attention during the last half of the 20th century when tamoxifen was approved by the FDA as the first selective estrogen receptor modulator (SERM). Endocrine therapy that has been found to be effective against breast cancer can be an option for ovarian cancer. It is now established that global changes in the epigenetic landscape are not only the hallmark of tumor development but also contribute to the development of resistance to hormone therapy. A set of functionally related genes involved in epigenetic reprogramming are controlled by specific transcription factors (TFs). Thus, the activities of TFs mediate important mechanisms through which epigenetic enzymes and co-factors modify chromatin for the worst outcome in a site-specific manner. Furthermore, the role of epigenetic aberrations involving histone modifications is established in ovarian cancer pathogenesis. This review aims to provide insights on the role of key epigenetic determinants of response as well as resistance to the hormone therapy, the current status of research along with its limitations, and future prospects of epigenetic agents as biomarkers in early diagnosis, prognosis, and personalized treatment strategies. Finally, the possibility of small phytoestrogenic molecules in combination with immunotherapy and epi-drugs targeting ovarian cancer has been discussed.